Potential Exposure and Cancer Risk from Formaldehyde Emissions from Installed Chinese Manufactured Laminate Flooring. Issue 6 (15th November 2017) - Sheehan, Patrick; Singhal, Ankur; Bogen, Kenneth T.; MacIntosh, David; Kalmes, Renee M.; McCarthy, John
Abstract: Lumber Liquidators (LL) Chinese‐manufactured laminate flooring (CLF) has been installed in >400, 000 U.S. homes over the last decade. To characterize potential associated formaldehyde exposures and cancer risks, chamber emissions data were collected from 399 new LL CLF, and from LL CLF installed in 899 homes in which measured aggregate indoor formaldehyde concentrations exceeded 100 μg/m 3 from a total of 17, 867 homes screened. Data from both sources were combined to characterize LL CLF flooring‐associated formaldehyde emissions from new boards and installed boards. New flooring had an average (± SD ) emission rate of 61.3 ± 52.1 μg/m 2 ‐hour; >one‐year installed boards had ∼threefold lower emission rates. Estimated emission rates for the 899 homes and corresponding data from questionnaires were used as inputs to a single‐compartment, steady‐state mass‐balance model to estimate corresponding residence‐specific TWA formaldehyde concentrations and potential resident exposures. Only ∼0.7% of those homes had estimated acute formaldehyde concentrations >100 μg/m 3 immediately after LL CLF installation. The TWA daily formaldehyde inhalation exposure within the 899 homes was estimated to be 17 μg/day using California Proposition 65 default methods to extrapolate cancer risk (below the regulation "no significant risk level" of 40 μg/day). Using a U.S. Environmental Protection Agency linear cancer risk model, 50th and 95th percentile values of expected lifetime cancer risk for residents of these homes were estimated to be 0.33 and 1.2 per 100, 000 exposed, respectively. Based on more recent data and verified nonlinear cancer risk assessment models, LL CLF formaldehyde emissions pose virtually no cancer risk to affected consumers.